Autophagy: Shedding Light on the Mechanisms and Multifaceted Roles in Cancers - Hongmei You; Ling Wang; Hongwu Meng; Jun Li; Guoying Fang (Biomolecules, 2025)
Autophagy, an evolutionarily conserved self-degradation catabolic mechanism, is crucial for recycling breakdown products and degrading intracellular components such as cytoplasmic organelles, macromolecules, and proteins in eukaryotes. The process, which can be selective or non-selective, involves the removal of specific ribosomes, protein aggregates, and organelles. Although the specific mechanisms governing various aspects of selective autophagy have not been fully understood, numerous studies have revealed that the dysregulation of autophagy-related genes significantly influences cellular homeostasis and contributes to a wide range of human diseases, particularly cancers, neurodegenerative disorders and inflammatory diseases. Notably, accumulating evidence highlights the complex, dual role of autophagy in cancer development. Thus, this review systematically summarizes the molecular mechanisms of autophagy and presents the latest research on its involvement in both pro- and anti-tumor progression. Furthermore, we discuss the role of autophagy in cancer development and summarize advancement in tumor therapies targeting autophagy.